Math, asked by karansinghsaggu, 2 months ago

Solve :- tanmx + cotpx = 0

Please explain with full explanation. ​

Answers

Answered by mathdude500
6

\large\underline{\sf{Solution-}}

Given Trigonometric equation is

\rm :\longmapsto\:tanmx + cotpx = 0

can be rewritten as

\rm :\longmapsto\:\dfrac{sin \: mx}{cos \: mx}  + \dfrac{cos \: px}{sin \: px}  = 0

\rm :\longmapsto\:\dfrac{sin \: mx \: sin \: px +  \: cos \: px \: cos \: mx}{cos \: mx}= 0

can be rewritten as

\rm :\longmapsto\:sin \: mx \: sin \: px +  \: cos \: px \: cos \: mx= 0

We know,

\boxed{ \tt{ \: cosx \: cosy \:  +  \: sinx \: siny \:  =  \: cos(x - y) \:  \: }}

So, using this identity, we get

\rm :\longmapsto\:cos(px - mx) = 0

\rm :\longmapsto\:cos(p - m)x = 0

We know,

\boxed{ \tt{ \: cosx = 0 \bf\implies \: \sf x = (2n + 1)\dfrac{\pi}{2}\: \forall \: n \in \: Z}}

So, using this, we get

\bf\implies \:(p - m)x = (2n + 1)\dfrac{\pi}{2}\: \forall \: n \in \: Z

 \red{\bf\implies \:\boxed{ \tt{ \: x = (2n + 1)\dfrac{\pi}{2(p - m)}\: \forall \: n \in \: Z}}}

More to Know :-

 \purple{\begin{gathered}\begin{gathered}\boxed{\begin{array}{c|c} \bf T-eq & \bf Solution \\ \frac{\qquad \qquad}{} & \frac{\qquad \qquad}{} \\ \sf sinx = 0 & \sf x = n\pi  \: \forall \: n \in \: Z\\ \\ \sf cosx = 0 & \sf x = (2n + 1)\dfrac{\pi}{2}\: \forall \: n \in \: Z\\ \\ \sf tanx = 0 & \sf x = n\pi\: \forall \: n \in \: Z\\ \\ \sf sinx = siny & \sf x = n\pi + {( - 1)}^{n}y \: \forall \: n \in \: Z\\ \\ \sf cosx = cosy & \sf x = 2n\pi \pm \: y\: \forall \: n \in \: Z\\ \\ \sf tanx = tany & \sf x = n\pi + y \: \forall \: n \in \: Z\end{array}} \\ \end{gathered}\end{gathered}}

Answered by XxitsmrseenuxX
23

Answer:

\large\underline{\sf{Solution-}}

Given Trigonometric equation is

\rm :\longmapsto\:tanmx + cotpx = 0

can be rewritten as

\rm :\longmapsto\:\dfrac{sin \: mx}{cos \: mx}  + \dfrac{cos \: px}{sin \: px}  = 0

\rm :\longmapsto\:\dfrac{sin \: mx \: sin \: px +  \: cos \: px \: cos \: mx}{cos \: mx}= 0

can be rewritten as

\rm :\longmapsto\:sin \: mx \: sin \: px +  \: cos \: px \: cos \: mx= 0

We know,

\boxed{ \tt{ \: cosx \: cosy \:  +  \: sinx \: siny \:  =  \: cos(x - y) \:  \: }}

So, using this identity, we get

\rm :\longmapsto\:cos(px - mx) = 0

\rm :\longmapsto\:cos(p - m)x = 0

We know,

\boxed{ \tt{ \: cosx = 0 \bf\implies \: \sf x = (2n + 1)\dfrac{\pi}{2}\: \forall \: n \in \: Z}}

So, using this, we get

\bf\implies \:(p - m)x = (2n + 1)\dfrac{\pi}{2}\: \forall \: n \in \: Z

 \red{\bf\implies \:\boxed{ \tt{ \: x = (2n + 1)\dfrac{\pi}{2(p - m)}\: \forall \: n \in \: Z}}}

More to Know :-

 \purple{\begin{gathered}\begin{gathered}\boxed{\begin{array}{c|c} \bf T-eq & \bf Solution \\ \frac{\qquad \qquad}{} & \frac{\qquad \qquad}{} \\ \sf sinx = 0 & \sf x = n\pi  \: \forall \: n \in \: Z\\ \\ \sf cosx = 0 & \sf x = (2n + 1)\dfrac{\pi}{2}\: \forall \: n \in \: Z\\ \\ \sf tanx = 0 & \sf x = n\pi\: \forall \: n \in \: Z\\ \\ \sf sinx = siny & \sf x = n\pi + {( - 1)}^{n}y \: \forall \: n \in \: Z\\ \\ \sf cosx = cosy & \sf x = 2n\pi \pm \: y\: \forall \: n \in \: Z\\ \\ \sf tanx = tany & \sf x = n\pi + y \: \forall \: n \in \: Z\end{array}} \\ \end{gathered}\end{gathered}}

Similar questions